Procurement and Inventory Control Mechanisms for Critical Raw Materials in Semiconductor Supply Chains - Li, Boqing (Journal Europeen des Systemes Automatises, 2025)
With the continuous advancement of global technological innovation, the semiconductor industry-serving as a fundamental enabler of information technology, telecommunications, automotive systems, and other sectors-has been increasingly challenged by complex supply chain management issues. Particular difficulties have emerged in the procurement and inventory control of critical raw materials, where firms are required to manage uncertainties in supply, fluctuations in demand, and risks associated with global market volatility. While existing studies have predominantly focused on optimizing isolated segments of the semiconductor supply chain-such as inventory control models based on demand forecasting or procurement strategies-the effectiveness of these traditional approaches is often constrained under conditions of high complexity and uncertainty. In response, this study aims to investigate the mechanisms for the procurement and inventory control of critical raw materials within the semiconductor supply chain. Emphasis is placed on enhancing supply chain resilience and responsiveness by optimizing procurement decisions and inventory management strategies. The research is structured around two primary themes: procurement of critical raw materials and strategic inventory control mechanisms in semiconductor supply chains. The findings are expected to contribute to the theoretical enrichment of supply chain management literature and to provide practical guidance for semiconductor enterprises operating in volatile market environments.